Dying Critically Ill Patients: A Caring Model Development based on a Muslim Perspective in Emergency Room, Naradhiwasrajanakarindra Hospital - แดงสุวรรณ กฤตยา; ฟองสุวรรณ ชฎาพร; มาแจ บาซอรี; จิบูละ อาดีละห์ (Princess of Naradhiwas University Journal, 2018)
This action research aimed to develop a caring model for dying critically ill patients in Emergency Room (ER), based on a Muslim perspective, in Naradhiwasrajanakarindra hospital. The participants of this study were 25 ER nurses and 30 Muslim family members of the dying critically ill patients in emergency room, Naradhiwasrajanakarindra hospital. Framework of this caring model integrated the manual for cardiopulmonary resuscitation (CPR) by Thai Resuscitation Council, as well as customs and rites of Islam. Main instruments were: 1) a checklist in using the caring model for nurses, 2) a checklist in using the caring model for family members, and 3) a questionnaire regarding satisfaction toward the using of caring model. They were tested for reliability of psychometric properties with Pearson correlation (0.83), and with Cronbach’s alpha coefficient both for the family members (0.84) and the registered nurses’ satisfaction (0.75). Results indicated that the caring model was congruent with Muslim perspective, and this, from the preparation step for CPR to the step of allowing family members to recover the human remains. In conclusion, the model integrates proper CPR practice, and Muslim traditions for dying critically ill patients in emergencyroom, in all respect for the spiritual and religious dimensions.